Zur Theorie der Hyperflächen in metrischen Linienelementraum mit euklidischen Zusammenhang - Bliznikas, V. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Близникас, К теории гиперповерхностей метрического пространства линейных элементов с евклидовой связностью V. Bliznikas, Euklidinio sąryšio metrinės tiesinių elementų erdvės hiperpaviršių teorijos klausimu